The Impact of Scenarios on the Performance of Entrepreneurial Imaginativeness: Evidence From an Experiment - Chen, Yang; Wang, Min; Liu, Yawen; Lu, Ruoyu (Frontiers in Psychology, 2022)
With the advent of the era of artificial intelligence, "scenario" frequently appears in new product development and has gradually become an effective tool gradually for analyzing user needs. However, the reasons for this phenomenon have not been explored in depth. New product development is a creative activity that requires product designers to imagine how people to live in the near future. So, we speculated that a familiar scenario that match designers’ background (including knowledge, expertise and experience) can spark their entrepreneurial imaginativeness by empathic simulation, and conducted an experiment to research the impact of scenarios on the performance of entrepreneurial imaginativeness. Results of this study confirmed that a familiar scenario did indeed inspire entrepreneurial imaginativeness more than an unfamiliar scenario, especially for high entrepreneurial imaginativeness. This study provided a new respective for understanding the relationship between empathy process and entrepreneurial opportunity recognition and evaluation processes and had practical implications for entrepreneurial practice, especially those that make human life better based on new digital technologies. Finally, we gave some suggestions on enhancing individuals’ entrepreneurial imaginativeness through different familiar scenarios and improving the team performance on creative tasks.